2011
DOI: 10.1002/hep.24227
|View full text |Cite
|
Sign up to set email alerts
|

New staging system and a registry for perihilar cholangiocarcinoma

Abstract: Perihilar cholangiocarcinoma is one of the most challenging diseases with poor overall survival. The major problem for anyone trying to convincingly compare studies among centers or over time is the lack of a reliable staging system. The most commonly used system is the Bismuth-Corlette classification of bile duct involvement, which, however, does not include crucial information such as vascular encasement and distant metastases. Other systems are rarely used because they do not provide several key pieces of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
204
1
15

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(223 citation statements)
references
References 59 publications
(74 reference statements)
3
204
1
15
Order By: Relevance
“…By specifically focusing on predicting resectability and outcomes, the Memorial Sloan Kettering Cancer Center group proposed a staging system that classifies pCCA on the basis of the local tumour extension, site of bile duct involvement, portal vein invasion and hepatic lobar atrophy, although the size of the remnant liver is not specified 232 . In 2011, the Mayo Clinic proposed a staging system comprising the tumour size, the extent of the disease in the biliary system, the involvement of the hepatic artery and portal vein, the involvement of lymph nodes, distant metastasis and the volume of the putative remnant liver after resection 233 . Although complex, this classification has the merit of finely defining surgical options, standardizing prospective reporting of pCCA and discriminating between prognostic classes.…”
Section: Staging Systemsmentioning
confidence: 99%
“…By specifically focusing on predicting resectability and outcomes, the Memorial Sloan Kettering Cancer Center group proposed a staging system that classifies pCCA on the basis of the local tumour extension, site of bile duct involvement, portal vein invasion and hepatic lobar atrophy, although the size of the remnant liver is not specified 232 . In 2011, the Mayo Clinic proposed a staging system comprising the tumour size, the extent of the disease in the biliary system, the involvement of the hepatic artery and portal vein, the involvement of lymph nodes, distant metastasis and the volume of the putative remnant liver after resection 233 . Although complex, this classification has the merit of finely defining surgical options, standardizing prospective reporting of pCCA and discriminating between prognostic classes.…”
Section: Staging Systemsmentioning
confidence: 99%
“…For this reason, an international working group was constituted with the aim to design a new staging system and registry for these tumors. The results of this project were published in 2011, proposing a new classification for Klatskin tumors using some parameters from previous staging systems [24] ( Table 3). The BC classification is kept for the assessment of the bile duct (which is labeled ''B'' for bile duct or Bismuth); the letters ''a'' and ''b'' are omitted and are replaced by ''R'' (for right hepatic duct) and ''L'' (for left hepatic duct; Figure 3A).…”
Section: T1mentioning
confidence: 99%
“…A new system has been proposed recently that was designed to assist with more accurate pre-or postoperative staging of the PCC. 28 This staging system, besides ductal involvement, incorporates more parameters in PCC staging: 1) tumor size (< 1 to > 3 cm in size), 2) tumor type (sclerosing, MF, mixed and polypoid or IG), 3) involvement of portal vein (PV) or hepatic artery (HA), 4) involvement of regional and distant LN, 5) remnant liver volume after resection, and 6) underlying liver disease such as fibrosis and PSC. More recently, the BC, MSKCC and TNM systems were compared in patients with PCC and it was found that TNM and MSKCC systems, tumor differentiation, LN status, distant metastases and R status were significantly correlated with survival, whereas BC classification, age, gender, jaundice, and upper abdominal pain were not.…”
Section: Perihilar Cholangiocarcinomamentioning
confidence: 99%